2017
DOI: 10.1134/s1607672917050052
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight compounds with anticoagulant activity from the scorpion Heterometrus laoticus venom

Abstract: Low-molecular-weight compounds with anticoagulant activity were isolated from the scorpion Heterometrus laoticus venom. The determination of the structure of the isolated compounds by nuclear magnetic resonance and mass spectrometry showed that one of the isolated compounds is adenosine, and the other two are dipeptides leucyl-tryptophan and isoleucyl-tryptophan. The anticoagulant properties of adenosine, which is an inhibitor of platelet aggregation, is well known, but its presence in scorpion venom is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The most abundant fraction, 5.21 (Figure 1), was also purified under conditions used for purification of fraction 5.22 and the structure of purified compound was analyzed as well. Analysis of purified substances indicated that fraction 5.5 corresponds to adenosine, fraction 5.21—to dipeptide LeuTrp and fraction 5.22—to dipeptide IleTrp [17]. The large quantities of dipeptides were prepared by peptide synthesis and their anticoagulant activity was analyzed in detail.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most abundant fraction, 5.21 (Figure 1), was also purified under conditions used for purification of fraction 5.22 and the structure of purified compound was analyzed as well. Analysis of purified substances indicated that fraction 5.5 corresponds to adenosine, fraction 5.21—to dipeptide LeuTrp and fraction 5.22—to dipeptide IleTrp [17]. The large quantities of dipeptides were prepared by peptide synthesis and their anticoagulant activity was analyzed in detail.…”
Section: Resultsmentioning
confidence: 99%
“…The anticoagulant activity of both dipeptides on the whole mice blood was determined by the Burker’s method [19], and when tested on the whole blood, the synthetic dipeptides showed significant increases in clotting time [17]. To study anticoagulant activity, the synthetic dipeptides were injected into the lateral vein of the mouse tail at a dose of 7.8 nmoles/g, which corresponds to maximal calculated concentration of 110 µM in the peripheral blood.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations